Crystal growth and superconducting properties of (Y,Ca)Ba2Cu3O7-delta with BaF2 additive - Chen, C; Wondre, F; Chowdhury, A; Hodby, J; Ryan, J (2000)
High-quality single crystals of YBCO:Ca up to 2x2cm in size have been grown in non-contaminating yttria or BaZrO3 crucibles from the eutectic self-flux system with BaF2 additive. A cluster model is proposed to describe the function of F- ions in the high temperature solution. The distribution coefficient of Ca between the solid and the liquid phases is much less than1, which indicates that crystals with a Ca doping level > 0.22 are thermodynamically unfavourable. The preference of six-fold co-ordination for Ca substituted in Y-sites at low doping concentration has little effect on the lattice parameters, but it distorts the conductive Cu-O layers. At high doping concentration, a small fraction of Ca also substitutes into Ba-sites near the Cu-O chains. We propose a modified model for estimating the effective hole concentration which fits better the universal parabolic variation of T-C.